PENGGUNAAN STRATEGI PEMBELAJARAN AKTIF DALAM MENINGKATKAN KONSENTRASI BELAJAR SISWA KELAS III PEMBELAJARAN TEMATIK DI SDN 22 SULUR MEDAN DESA SUMBER HARAPANKECAMATAN SAMBAS KABUPATEN SAMBASTAHUN PELAJARAN 2024-2025 - Yeni Sari; Yayan Ridwan; Meriyanti (CV. Adiba Aisha Amira, 2025)
The purpose of this study is to describe: 1) The implementation of teachers implementing active learning strategies in improving the concentration of third grade students in thematic learning at SDN 22 Sulur Medan, Sumber Harapan Village, Sambas District, Sambas Regency in the 2024-2025 academic year; 2) The implications of using active learning strategies in improving the concentration of third grade students in thematic learning at SDN 22 Sulur Medan, Sumber Harapan Village, Sambas District, Sambas Regency in the 2024-2025 academic year; and 3) Factors that influence the concentration of students in learning in third grade at SDN 22 Sulur Medan, Sumber Harapan Village, Sambas District, Sambas Regency in the 2024-2025 academic year. This study uses qualitative research with a phenomenological research type. Data collection techniques used observation, interviews, and documentation. Data analysis techniques used were data collection, data reduction, data presentation, and drawing conclusions. Data validity techniques used were triangulation and member check techniques. The results of this study indicate that: (1) The implementation of teachers applying active learning strategies in improving the concentration of learning of class III students in Thematic learning at SDN 22 Sulur Medan. The application of active learning strategies at SDN 22 Sulur Medan through the role of teachers as motivators, facilitators, and effective class managers. (2) Implications of the Use of Active Learning Strategies in Improving the Concentration of Third Grade Students in Thematic Learning at SDN 22 Sulur Medan, where student understanding increases through the use of visual media and clear delivery of learning objectives, active involvement, and collaboration between teachers and principals in creating a better learning experience for students. (3) Factors Affecting the Concentration of Third Grade Students in Thematic Learning at SDN 22 Sulur Medan are influenced by internal and external factors.